2020
DOI: 10.1101/2020.05.15.20103473
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Development and validation of chest CT-based imaging biomarkers for early stage COVID-19 screening

Abstract: Coronavirus Disease 2019 (COVID-19) is currently a global pandemic, and the early screening of COVID-19 is one of the key factors for COVID-19 control and treatment. Here, we developed and validated chest CT-based imaging biomarkers for COVID-19 patient screening. We identified the vasculature-like signals from CT images and found that, compared to healthy and community acquired pneumonia (CAP) patients, the COVID-19 patients revealed significantly higher abundance of these signals. Furthermore, unsupervised f… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…To date, many studies have reported the detection of COVID-19 in patients suspected of infection. 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 For instance, Menni et al. 16 reported the efficiency of self-reported symptoms in early identification of potential COVID-19.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To date, many studies have reported the detection of COVID-19 in patients suspected of infection. 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 For instance, Menni et al. 16 reported the efficiency of self-reported symptoms in early identification of potential COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…To date, many studies have reported the detection of COVID-19 in patients suspected of infection. [15][16][17][18][19][20][21][22][23][24][25] For instance, Menni et al 16 reported the efficiency of self-reported symptoms in early identification of potential COVID-19. This allows medical providers to timely admit all potential COVID-19 cases to hospitals in countries and territories where medical resources are relatively adequate, such as China.…”
Section: Accessmentioning
confidence: 99%
See 1 more Smart Citation